Genetic Polymorphisms in FAS (CD95) and FAS Ligand (CD178) Promoters and Risk of Tobacco-related Oral Carcinoma: Gene–Gene Interactions in High-risk Indians. (25th January 2013) - Karimi, Mohammad Yahya; Kapoor, Vaishali; Sharma, Suresh Chandra; Das, Satya Narayan
<x xml:space="preserve">Abstract</x> We assessed the association of functional single nucleotide polymorphisms (SNP) in FAS -1377, -670 and FAS ligand (FASL) -844 promoters in 139 oral cancer patients and 126 normal subjects by PCR-RFLP. In logistic regression analysis FAS -1377 GA genotype appeared to marginally increase the risk while FASL -844 TC genotype appeared as low risk factor. The combined genotypes FAS -1377 GA or AA and FASL -844 TT (p <0.03), and FAS -670 AG or GG and FASL -844 TT (p <0.007) appeared to double the risk. FAS and FASL gene–gene and gene–environment interactions seems to modulate susceptibility/resistance to tobacco-related oral cancer in Indians.